A novel mutation in human EMD gene and mitochondrial dysfunction in emerin knockdown cardiomyocytes. Issue 19 (15th September 2022) - Du, Zunhui; Zhu, Tinfang; Lin, Menglu; Bao, Yangyang; Qiao, Jing; Lv, Gang; Xie, Yinyin; Li, Qihen; Quan, Jinwei; Xu, Cathy; Xie, Yuan; Wang, Lingjie; et al.
Abstract: Emerin is an inner nuclear envelope protein encoded by the EMD gene, mutations in which cause Emery–Dreifuss muscular dystrophy type 1 (EDMD1). Cardiac involvement has become a major threat to patients with EDMD1; however, the cardiovascular phenotype spectrums of emerinopathy and the mechanisms by which emerin regulates cardiac pathophysiology remain unclear. Here, we identified a novel nonsense mutation (c.C57G, p.Y19X) in the EMD gene in a Han Chinese family through high‐throughput sequencing. Two family members were found to have EDMD1 with muscle weakness and cardiac arrhythmia. Mechanistically, we first discovered that knockdown of emerin in HL‐1 or H9C2 cardiomyocytes lead to impaired mitochondrial oxidative phosphorylation capacity with downregulation of electron transport chain complex I and IV and upregulation of complex III and V. Moreover, loss of emerin in HL‐1 cells resulted in collapsed mitochondrial membrane potential, altered mitochondrial networks and downregulated multiple factors in RNA and protein level, such as PGC1α, DRP1, MFF, MFN2, which are involved in regulation of mitochondrial biogenesis, fission and fusion. Our findings suggest that targeting mitochondrial bioenergetics might be an effective strategy against cardiac disorders caused by EMD mutations.